An evaluation of central penetration from a peripherally administered oxytocin receptor selective antagonist in nonhuman primates. Issue 1 (1st January 2017) - Smith, Aaron L.; Walum, Hasse; Connor-Stroud, Fawn; Freeman, Sara M.; Inoue, Kiyoshi; Parr, Lisa A.; Goodman, Mark M.; Young, Larry J.
Graphical abstract: Abstract: The physiology of the oxytocin receptor has increasingly become a focus of scientific investigation due to its connection with social behavior and psychiatric disorders with impairments in social funciton. Experimental utilization of small molecule and peptide antagonists for the oxytocin receptor has played a role in deciphering these biological and social behavior connections in rodents. Described herein is the evaluation of a potent and selective oxytocin receptor antagonist, ALS-I-41, and details to consider for its use in nonhuman primate behavioral pharmacology experiments utilizing intranasal or intramuscular administration. The central nervous system penetration and rate of metabolism of ALS-I-41 was investigated via mass spectroscopy analysis of cerebrospinal fluid and plasma in the rhesus macaque after intranasal and intramuscular administration. Positron emission tomography was also utilized with [ 18 F] ALS-I-41 in a macaque to verify observed central nervous system (CNS) penetration and to further evaluate the effects of administration rate on CNS penetration of Sprague-Dawley rats in comparison to previous studies.